As variedades no jornalismo brasileiro - Assis, Francisco de (2009)
What characterizes variety journalism in the Brazilian press? What gives identity to notebooks and cultural sections that focus on leisure and cover entertainment? Are the genres and journalistic formats? Or are the thematic contents? What are the parameters for understanding how the culture and entertainment guidelines have been appropriated by newspapers published in the country? To answer these questions, the form and content of five regional publications - Diário do Nordeste, People's Mail, Valeparaibano, Now São Paulo and Gazeta do Tatuapé -, as well as a nationally prestigious journal - Folha de S.Paulo. Opting for the mixed method of research - quantitative and qualitative - the investigation maps, besides the genres, the political geography, the cultural cartography and the themes of the current subjects in the aforementioned spaces, in order to establish comparisons. The results indicate a diversity of productions, which respect the singularities of the regions in which they operate. In general, it can be said that in variety publishing, there are both subjects common to cultural journalism - music, visual arts, performing arts, cinema, etc. - on matters of television attractions, celebrities, behavioral tendencies and other entertainment issues, taking up significant space on the pages of print. As a reflection of the vehicles' preference for a journalistic production focused on the cultural industry and the media shows, the culture mass was predominant in all publications analyzed. However, even if the focus of variety journalism is on fun, this specialty is not characterized as an entertainment product; What she does is guide how and where to have fun. Not by chance, it was found that the journalistic genres of the space in question, with few exceptions, are limited to the informative and the utilitarian. Much more than generating culture and entertainment, varieties play the role of leisure guide. (AU)